1971
DOI: 10.1002/bjs.1800580104
|View full text |Cite
|
Sign up to set email alerts
|

Ileus: The restoration of alimentary-tract motility by pharmacological means

Abstract: The nature of ileus and the clinical problem it poses are discussed. A consideration of the previous multiplicity of treatments is presented. The concepts behind the present mode of treatment are outlined. This consists of removing the sympathetic inhibition of the alimentary tract in the condition and potentiating or supplementing tone. Case histories are presented to illustrate the use of the drugs suggested, and the indications for therapy are discussed. The mistaken concept that the gut is “paralysed” in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

1976
1976
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(32 citation statements)
references
References 67 publications
1
30
0
1
Order By: Relevance
“…This finding is in agreement with previous reports which outlined the existence of intestin al movements early in the postoperative period with various techniques: balloon kymography [19,20,22], radiological methods [16,18,21] or study of abdominal sounds [1,6,25,27]. Therefore, it may be suggest ed that the 'physiological' ileus is not due to the disappearance of intes tinal mechanical activities but to their disorganization.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This finding is in agreement with previous reports which outlined the existence of intestin al movements early in the postoperative period with various techniques: balloon kymography [19,20,22], radiological methods [16,18,21] or study of abdominal sounds [1,6,25,27]. Therefore, it may be suggest ed that the 'physiological' ileus is not due to the disappearance of intes tinal mechanical activities but to their disorganization.…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, a large number of means have been proposed for stimulating the intestinal motility during the postoperative period [20]. However, no effective therapeutic measure has been reported, inasmuch as the methods for studying intestinal motility were often too complex and approximative for permitting an evaluation of the effects of such therapies.…”
mentioning
confidence: 99%
“…The cause of postoperative ileus remains only partly understood, and its treatment remains often empirical and suboptimal. Attempts by various prokinetics (such as acetylcholine, cisapride, or even motilides) to stimulates smooth muscle cells directly or via the efferent neural pathways frequently gave disappointing results (4,6,13,17,25). More recent studies suggested, however, that an inhibitory influence by afferent nerves could be involved in the genesis of postoperative ileus.…”
Section: Discussionmentioning
confidence: 99%
“…It increases parasympathetic activity which leads to hyperperistalsis. Neostigmine was first tried by Neely and Catchpole three decades ago in small bowel paralytic ileus [54] . Neostigmine is given intravenously and has a rapid onset [1-20 min] and short duration of action [1-2 hrs] [55] .…”
Section: Medical Treatmentmentioning
confidence: 99%